Risk factors associated with the frailty syndrome: Moravian Association´s care programs for the elderly adults - Ugalde Castillo, Francinie Eugenia (2020)
Purpose: To determine the potential risk factors associated with the frailty syndrome in elderly persons who attended the programs of the Moravian Association (local networking of the Progressive Care Networking for the Elderly Persons, Nazareth House and House of the Elderly Person) in Moravia, during the second semester of 2018. Method: Observational, cross-association transverse descriptive study. The population was composed of 174 elderly persons who are beneficiaries of the local programs in charge of the Moravian Association; only 80 of them participated as the sample. Sociodemographic characteristics, physical, functional, and cognitive variables were evaluated using previously validated scales, likewise, frailty criteria were analyzed by examining the Fried phenotype. A non-parametric inferential analysis using the ANOVA test, an explanatory linear regression model as well as the corresponding Prevalence Odds Ratio (statistical significance at p≤0.05 for all cases) were carried out.  Results: A prevalence of 52.2% of frailty and 46.3% of pre-frailty was found; only 1.5% of the subjects did not present any grade of the syndrome. A significant link between the following risk factor was identified: females aged over 80 years, being institutionalized for more than three years, CVD, COPD, anemia, arthritis, dementia, polypharmacy, lack of support networks and low schooling.  Conclusions: There was a high prevalence of frailty syndrome even in early stages of aging. Weakness and low walking speed were the most common manifestation of the phenotype. The evolution of frailty syndrome is progressive, multifactorial and multisystemic.